Analysis of the Effect of Long-Term and Short-Term Debt on Company Asset Growth - Sania, Flora; Wibisono, Fayakhun; Sagala, Mohammad Hafidz; Namira, Pasya; Aliyah, Nur (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aims to analyze the effect of short-term debt and long-term debt on asset growth. Debt is an important form of external financing for companies to support their operational activities and asset expansion. Short-term debt is used to meet working capital needs, while long-term debt is used to finance long-term investments. This study uses a quantitative method with secondary data obtained from the financial reports of companies listed on the Indonesia Stock Exchange. This analysis was conducted using multiple linear regression to test the partial and simultaneous effects of variables on asset growth. The results show that short-term debt has a positive effect on asset growth because it can increase a company's working capital, while long-term debt affects the effectiveness of its use. A balanced financing structure of short-term and long-term debt is very important for optimal asset growth.